2016
DOI: 10.1371/journal.pone.0149494
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MazF-Mediated Sequence-Specific RNA Cleavage in Pseudomonas putida Using Massive Parallel Sequencing

Abstract: Under environmental stress, microbes are known to alter their translation patterns using sequence-specific endoribonucleases that we call RNA interferases. However, there has been limited insight regarding which RNAs are specifically cleaved by these RNA interferases, hence their physiological functions remain unknown. In the current study, we developed a novel method to effectively identify cleavage specificities with massive parallel sequencing. This approach uses artificially designed RNAs composed of diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 50 publications
0
63
0
Order By: Relevance
“…To the best of our knowledge, this is the first MazF that specifically recognizes the U^ACA sequence (Masuda & Inouye, ; Schifano & Woychik, ). Recently, Zorzini et al., () determined the crystal structure of E. coli MazF (MazFec) in complex with the substrate analogue d(A 1 U 2 A 3 C 4 A 5 U 6 A 7 ), and reinforced the notion that MazFec recognizes ACA triplet strictly and that MazFec cleaves the substrate at the position of ^ACA and A^CA (Miyamoto et al., ; Vesper et al., ; Zhang, Zhang, Hara, Kato, & Inouye, a; Zhang et al., ). They mentioned that the MazFec recognition site could be divided into two different regions: first, the one where dU 2 is located, which is called the upstream binding site; and second, the one that accommodates d(A 3 C 4 A 5 U 6 ), which is called the downstream binding groove.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first MazF that specifically recognizes the U^ACA sequence (Masuda & Inouye, ; Schifano & Woychik, ). Recently, Zorzini et al., () determined the crystal structure of E. coli MazF (MazFec) in complex with the substrate analogue d(A 1 U 2 A 3 C 4 A 5 U 6 A 7 ), and reinforced the notion that MazFec recognizes ACA triplet strictly and that MazFec cleaves the substrate at the position of ^ACA and A^CA (Miyamoto et al., ; Vesper et al., ; Zhang, Zhang, Hara, Kato, & Inouye, a; Zhang et al., ). They mentioned that the MazFec recognition site could be divided into two different regions: first, the one where dU 2 is located, which is called the upstream binding site; and second, the one that accommodates d(A 3 C 4 A 5 U 6 ), which is called the downstream binding groove.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation, barcode ligation, and sequencing were performed as described previously (Miyamoto et al 2016a). The sequence data were analyzed with CLC Genomics 7.5.1., using the same parameters outlined in our previous work (Miyamoto et al 2016a).…”
Section: Cleavage Sequence Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of MazF homologues have subsequently been identified from bacteria to archaea, with some bacteria having more than one MazF homologue. The MazF homologues so far identified specifically cleave mRNAs at either 3-, 5-, or 7-base recognition sequences [Zhang et al, 2003a;Zhu et al, 2006Zhu et al, , 2008Zhu et al, , 2009Nariya and Inouye, 2008;Park et al, 2011;Miyamoto et al, 2016]. It was indicated that the physiological role of these MazF homologues differs in each species, making the deciphering of cleavage sequence important to reveal the detailed mechanism of MazF.…”
Section: Introductionmentioning
confidence: 99%